The Traditional Settlement Pattern in Kotagede and Their impact on Human activities and Behavior - Aljamal, Siefaddeen; Raharjo, Wiryono (International Journal of Architecture and Urbanism, 2025)
Planner and settlement patterns have an impact on how communities behave and appear; these are brought on by a variety of factors that have an impact on us as humans and how we respond to our capitulating environment. The majority of us live in modern or typical settlement patterns where we have our own privacy, don't share our land with others, and have regular roads where we can park and move around freely while using our natural means of transportation. The concept of traditional Javanese houses is different from all of that because the latter prioritize effectiveness in the case of a faction war. This study aims to shed light on the settlement patterns in Kotagede communities and the significance of applying the spatial concepts of traditional Javanese homes. The primary documents used in this qualitative research, which is described in descriptive manner using any supporting illustrations or photos, were discovered through literature reviews of both books and journals. Understanding the settlement pattern and housing of the Javanese communities in Kotagede and how it affects behavior is the outcome of this study.